Use of Complementary and Alternative Medicine in the context of cancer; prevalence, reasons for use, disclosure, information received, risks and benefits reported by people with cancer in Norway - Agnete E. Kristoffersen; Jorunn V. Nilsen; Trine Stub; Johanna Hök Nordberg; Barbara Wider; Dana Mora; Kiwumulo Nakandi; Mona Bjelland (BMC, 2022)
Abstract Background Research exploring the use of specific Complementary and Alternative Medicine (CAM) modalities by Norwegian cancer patients is sparse. The aims of this study were therefor to map the different CAM modalities cancer patients use and further investigate their rationale for use, communication about use, self-reported benefits and harms, and their sources of information about the different modalities. Methods In cooperation with the Norwegian Cancer Society (NCS), we conducted an online cross-sectional study among members of their user panel with present or previously cancer (n = 706). The study was carried out in September/October 2021 using a modified cancer-specific version of the International Questionnaire to Measure Use of Complementary and Alternative Medicine (I-CAM-Q). In total, 468 members, 315 women and 153 men, agreed to participate resulting in a response rate of 67.2%. The study was reported in accordance with the National Research Center in Complementary and Alternative Medicine's (NAFKAM) model of reporting CAM use. Results A large proportion of the participants (79%, n = 346) had used some form of CAM with a mean of 3.8 modalities each (range 1-17); 33% (n = 143) had seen a CAM provider, 52% (n = 230) had used natural remedies, while 58% (n = 253) had used self-help practices. Most of the participants used CAM to increase their quality of life, cope with the cancer disease or for relaxation/well-being (64%-94%), mostly with high satisfaction and low rates of adverse effects. Few used CAM to treat cancer or prevent it from spreading (16%, n = 55). The main information sources were health care providers (47%), the internet (47%), and family and friends (39%). More than half (59%) of the cancer patients discussed their use of at least one CAM modality with a physician. Conclusions The results of this survey will provide health professionals with more in-depth insight into the patterns of CAM use by cancer patients and facilitate better-informed discussions with their patients. Considering the high use of CAM, reliable information provision supporting cancer care providers' knowledge and health literacy among patients as well as good communication are crucial. The cooperation between the NCS and NAFKAM provides an example of how to address these issues.